Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0141067
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of the Staphylococcus aureus and Staphylococcus epidermidis Secretomes Isolated from the Skin Microbiota of Atopic Children on CD4+ T Cell Activation

Abstract: Interactions between the immune system and skin bacteria are of major importance in the pathophysiology of atopic dermatitis (AD), yet our understanding of them is limited. From a cohort of very young AD children (1 to 3 years old), sensitized to Dermatophagoides pteronyssinus allergens (Der p), we conducted culturomic analysis of skin microbiota, cutaneous transcript profiling and quantification of anti-Der p CD4+ T cells. This showed that the presence of S. aureus in inflamed skin of AD patients was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 36 publications
4
62
0
2
Order By: Relevance
“…6), despite the absence of inflammatory cells and bone marrow destruction. While similar gene expression findings have been reported for S. aureus infections 37,38 and S. epidermidis in vitro and in vivo studies, 39,40 the lack of osteolysis in this osteoclastogenic environment remains largely unexplained and remains an important future research direction.…”
Section: S Epidermidis Inhibits Osseous Integrationsupporting
confidence: 68%
“…6), despite the absence of inflammatory cells and bone marrow destruction. While similar gene expression findings have been reported for S. aureus infections 37,38 and S. epidermidis in vitro and in vivo studies, 39,40 the lack of osteolysis in this osteoclastogenic environment remains largely unexplained and remains an important future research direction.…”
Section: S Epidermidis Inhibits Osseous Integrationsupporting
confidence: 68%
“…The generation of Tregs with enhanced suppressive activity was also reported in studies related to other pathogens (22,46) and may thus be a general phenomenon associated with infectious conditions. Nevertheless, a previous study showed that extracellular products of S. epidermidis promoted the suppressive activity of human Tregs (47), further indicating that this cell population may be involved in counterinflammatory mechanisms operating during infections with this bacterium. Tregs were recently shown to be crucial for establishing S. epidermidis skin commensalism (48).…”
Section: Discussionmentioning
confidence: 93%
“…However, cutaneous microbes may also be able to promote regulatory responses in adult mice, as exposure to a lysate of Vitreoscilla filiformis can promote the accumulation of T reg cells within the skin (Volz et al, 2014). Further, secreted products from S. epidermidis promotes IL-10 production by human dendritic cells (Laborel-Preneron et al, 2015) and skin exposure to TLR2-6 binding S. aureus derived lipopeptides can potently suppress immune responses via the induction of regulatory myeloid cells (Skabytska et al, 2014). The microbiota can also limit Thymic strmal lymphopoietin (TSLP) expression in mice with a defective skin barrier (Yockey et al, 2013).…”
Section: Induction Of Regulatory Responses By the Microbiotamentioning
confidence: 99%